Synthesis and Potent Antimalarial Activity of Kalihinol B - Daub, Mary Elisabeth; Prudhomme, Jacques; Le Roch, Karine; Vanderwal, Christopher D (Journal of the American Chemical Society, 2015)
Of the 50+ kalihinane diterpenoids reported to date, only five had been tested for antimalarial activity, in spite of the fact that kalihinol A is the most potent among the members of the larger family of antimalarial isocyanoterpenes. We have validated a strategy designed to access many of the kalihinanes with a 12-step enantioselective synthesis of kalihinol B, the tetrahydrofuran isomer of kalihinol A (a tetrahydropyran). Kalihinol B shows similarly high potency against chloroquine-resistant Plasmodium falciparum.